Azna Region Farmers' Perception of High-Risk Agriculture (A Grounded Theory) - Amrollah Keshavarz; Soraya Memar; Reza Hemmati; Ali ghanbaribarzain (توسعه اجتماعی)
Today, one of the prerequisites for sustainable development is the strengthening of the agricultural sector; because there is a close link between agriculture and sustainable development. The agricultural sector in the world has been subjected to serious environmental crises due to the transition from the traditional to the modern type. The purpose of this study is to analyze farmers' perceptions of conventional agriculture. The method used in this study is qualitative research and grounded theory strategy. A total of 33 semi-structured interviews were conducted for data collection. Initially, 72 concepts were extracted; after turning them into more abstract concepts, 7 central categories were obtained. The high-risk agricultural code, as the final selection code, is a representation of farmers' perceptions of conventional agriculture. According to the results of the present study, the study of the causes and factors of knowledge and practice gap in the use of chemical inputs and typology of patterns of chemical fertilizers and pesticides can be useful in agricultural policy making.